(untitled) (Dhaka University Law Journal, 2025)
Digital commerce and cross-border data flows are growing faster in an unprecedented way and scale in the era of Fourth Industrial Revolution (4IR). The digital era requires rethinking of traditional legislative policies in addressing governance of digital trade issues to achieve desired economic gains of innovation. Domestic favorable legal framework has always played pivotal role in leveraging technological transformation and economic growth. As a developing country, Bangladesh urgently requires a flexible regulatory regime with proper safeguards for both businesses and consumers. Moreover, domestic legal reform in Bangladesh is particularly necessary to address the issues of data privacy, e-payment, consumer protection, cybersecurity, and market competition. This article attempts to explore the key challenges of integrating digital trade within the existing operational domestic legal environment in Bangladesh and strives to figure out how the potential reforms can be done to seize the maximum opportunities arising from the data driven transformation of trade and digital economy. Dhaka University Law Journal, 2024, 35 (1), 235-263